2016
DOI: 10.1111/gbi.12201
|View full text |Cite
|
Sign up to set email alerts
|

Microbialite response to an anthropogenic salinity gradient in Great Salt Lake, Utah

Abstract: A railroad causeway across Great Salt Lake, Utah (GSL), has restricted water flow since its construction in 1959, resulting in a more saline North Arm (NA; 24%-31% salinity) and a less saline South Arm (SA; 11%-14% salinity). Here, we characterized microbial carbonates collected from the SA and the NA to evaluate the effect of increased salinity on community composition and abundance and to determine whether the communities present in the NA are still actively precipitating carbonate or if they are remnant fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 85 publications
(143 reference statements)
8
101
0
Order By: Relevance
“…While cyanobacteria have often been considered to be the dominant builders of microbial mats, Ley et al () demonstrated that Chloroflexi may also form the bulk of the biomass in some mat systems, and Johnson, Beddows, Flynn, and Osburn () found low abundances of Cyanobacteria , but high abundances of Proteobacteria , in microbialites of Laguna Bacalar. Non‐cyanobacterial builders have also been documented in microbialite communities in Pavilion Lake (Russell et al, ), Great Salt Lake (Lindsay et al, ), and Cuatro Ciénegas (Breitbart et al, ). Sulfate reducers, which have been found to play a role in microbialite formation in some systems (e.g., Baumgartner et al, ; Breitbart et al, ), are essentially absent from the DNA sequencing results, with the exception of a very small relative abundance (0.03%, FHN1) of the order Synthrophobacterales in one sample.…”
Section: Discussionmentioning
confidence: 98%
“…While cyanobacteria have often been considered to be the dominant builders of microbial mats, Ley et al () demonstrated that Chloroflexi may also form the bulk of the biomass in some mat systems, and Johnson, Beddows, Flynn, and Osburn () found low abundances of Cyanobacteria , but high abundances of Proteobacteria , in microbialites of Laguna Bacalar. Non‐cyanobacterial builders have also been documented in microbialite communities in Pavilion Lake (Russell et al, ), Great Salt Lake (Lindsay et al, ), and Cuatro Ciénegas (Breitbart et al, ). Sulfate reducers, which have been found to play a role in microbialite formation in some systems (e.g., Baumgartner et al, ; Breitbart et al, ), are essentially absent from the DNA sequencing results, with the exception of a very small relative abundance (0.03%, FHN1) of the order Synthrophobacterales in one sample.…”
Section: Discussionmentioning
confidence: 98%
“…Both open and closed-basin systems can host the formation of microbialites—characteristic sedimentary structures formed by the trapping of mineral detritus in the extracellular polymeric substances formed by microbial mats (Noffke et al, 2001). Active microbialite communities can be found in the closed-basin Great Salt Lake and the open-basin Pavilion Lake and modern stromatolite formations found in Shark Bay, Western Australia (Papineau et al, 2005; Russell et al, 2014, Lindsay et al, 2017). Microbially induced sedimentary structures are preserved and exceptionally well-studied in the modern Pilot Valley Basin, Utah, and on geologic timescales in the ancient Strelley Pool Chert stromatolites and Dresser Formation microbialites of the Archean-aged Pilbara Craton (Van Kranendonk et al 2003; Allwood, et al, 2006; Noffke et al, 2013; Russell et al, 2014; Lynch et al, 2015; Westall et al, 2015b; Lindsay et al, 2017).…”
Section: Mars Analog Environments On Earthmentioning
confidence: 99%
“…They have, in general, never been buried and (early) diagenetic processes have been carefully addressed in literature or are under investigation. Eardley (1938), Sandberg (1975), Currey and James (1982), Spencer et al (1984), Currey and Oviatt (1985), Pedone and Dickson (2000), Chidsey et al (2015), Bouton et al (2016aBouton et al ( , 2016b, Pace et al (2016), Lindsay et al (2017) Ries Crater lake (South Germany)…”
Section: Tablementioning
confidence: 99%